Contribution of microvascular dysfunction to chronic pain - Coderre, Terence J. (Frontiers in Pain Research, 2023)
There is growing evidence that microvascular dysfunction is a pathology accompanying various injuries and conditions that produce chronic pain and may represent a significant contributing factor. Dysfunction that occurs within each component of the microvasculature, including arterioles, capillaries and venules impacts the health of surrounding tissue and produces pathology that can both initiate pain and influence pain sensitivity. This mini review will discuss evidence for a critical role of microvascular dysfunction or injury in pathologies that contribute to chronic pain conditions such as complex regional pain syndrome (CRPS) and fibromyalgia.